RELIGIOUS BELIEFS IN SOGD IN THE EARLY MIDDLE AGES (TAMADDUN NURI JURNALI, 2024)
This article examines the religious landscape of Sogdiana in the early Middle Ages, when this region of Central Asia served as a crossroads of cultures and religions along the Silk Road. By examining archaeological finds, written sources and historical data, the authors of the article analyze how Zoroastrianism, Buddhism, Christianity and Islam coexisted and interacted in Sogd, contributing to the formation of the unique religious identity of the region.